THE POWERHOUSES OF THE ENDOCRINE SYSTEM: THYROID, PITUITARY, AND ADRENAL GLANDS - Praveenkumar Periyasamy; Arike Badaru; Krisli Serani; Tariq Rafique (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The endocrine system is a network of glands that produce hormones, which are chemical messengers released into the bloodstream to regulate various bodily functions. Key glands in this system include the thyroid, pituitary, and adrenal glands, often referred to as the "powerhouses" of the endocrine system. Objective: This article aims to discuss the anatomical structure and functioning of the thyroid, pituitary, and adrenal glands, highlighting their essential roles in maintaining hormonal balance. Additionally, it explores common disorders associated with each gland and current diagnostic and treatment methods. Methods: A comprehensive review of existing literature from PubMed and other reputable sources was conducted to compile information on the structure, function, and clinical significance of the thyroid, pituitary, and adrenal glands. Results: Thyroid Gland: Located in the neck, the thyroid gland produces hormones that control metabolism, growth, and development. These hormones regulate the function of most cells and organs in the body. Pituitary Gland: Known as the "master gland," the pituitary is located at the base of the brain and controls other endocrine glands, such as the thyroid and adrenal glands, by secreting stimulating hormones. Adrenal Glands: Situated atop the kidneys, the adrenal glands produce hormones like cortisol and adrenaline, which are crucial for stress management and maintaining homeostasis. Conclusion: Understanding the interconnected roles and hormonal interactions between the thyroid, pituitary, and adrenal glands is vital for comprehending their collective impact on the endocrine system. This review underscores the significance of these glands in human physiology and disease control by providing an extensive summary of their individual and combined functions, common disorders, and current diagnostic and treatment approaches.